Crosstalk among intestinal barrier, gut microbiota and serum metabolome after a polyphenol-rich diet in older subjects with "leaky gut": The MaPLE trial. Issue 10 (October 2021) - Peron, Gregorio; Gargari, Giorgio; Meroño, Tomás; Miñarro, Antonio; Lozano, Esteban Vegas; Escuder, Pol Castellano; González-Domínguez, Raúl; Hidalgo-Liberona, Nicole; Del Bo', Cristian; Bernardi, Stefano; Kroon, Paul Antony; Carrieri, Barbara; et al.
Summary: Background &aim: The MaPLE study was a randomized, controlled, crossover trial involving adults ≥60 y.o. (n = 51) living in a residential care facility during an 8-week polyphenol-rich (PR)-diet. Results from the MaPLE trial showed that the PR-diet reduced the intestinal permeability (IP) in older adults by inducing changes to gut microbiota (GM). The present work aimed at studying the changes in serum metabolome in the MaPLE trial, as a further necessary step to depict the complex crosstalk between dietary polyphenols, GM, and intestinal barrier. Methods: Serum metabolome was monitored using a semi-targeted UHPLC-MS/MS analysis. Metataxonomic analysis (16S rRNA gene profiling) of GM was performed on faecal samples. Clinical characteristics and serum levels of the IP marker zonulin were linked to GM and metabolomics data in a multi-omics network. Results: Compared to the control diet, the PR-diet increased serum metabolites related to polyphenols and methylxanthine intake. Theobromine and methylxanthines, derived from cocoa and/or green tea, were positively correlated with butyrate-producing bacteria (the order Clostridiales and the genera Roseburia, Butyricicoccus and Faecalibacterium ) and inversely with zonulin. A direct correlation between polyphenol metabolites hydroxyphenylpropionic acid-sulfate, 2-methylpyrogallol-sulfate and catechol-sulfate with Butyricicoccus was also observed, while hydroxyphenylpropionic acid-sulfate and 2-methylpyrogallol-sulfate negatively correlated with Methanobrevibacter . The multi-omics network indicated that participant's age, baseline zonulin levels, and changes in Porphyromonadaceae abundance were the main factors driving the effects of a PR-diet on zonulin. Conclusion: Overall, these results reveal the complex relationships among polyphenols consumption, intestinal permeability, and GM composition in older adults, and they may be important when setting personalized dietary interventions for older adults. Trial registration number: ISRCTN10214981.